The consensus rye microsatellite map with EST-SSRs transferred from wheat - D. O. Vidakovic; D. Perovic; T. V. Semilet; A. Börner; E. K. Khlestkina (Вавиловский журнал генетики и селекции)
Microsatellite (SSR) markers with known precise intrachromosomal locations are widely used for mapping genes in rye and for the investigation of wheat-rye translocation lines and triticale highly demanded for mapping economically important genes and QTL-analysis. One of the sources of novel SSR markers in rye are microsatellites transferable from the wheat genome. Broadening the list of available SSRs in rye mapped to chromosomes is still needed, since some rye chromosome maps still have just a few microsatellite loci mapped. The goal of the current study was to integrate wheat EST-SSRs into the existing rye genetic maps and to construct a consensus rye microsatellite map. Four rye mapping populations (P87/P105, N6/N2, N7/N2 and N7/N6) were tested with CFE (EST-SSRs) primers. A total of 23 Xcfe loci were mapped on rye chromosomes: Xcfe023, -136 and -266 on chromosome 1R, Xcfe006, -067, -175 and -187 on 2R, Xcfe029 and -282 on 3R, Xcfe004, -100, -152, -224 and -260 on 4R, Xcfe037, -208 and -270 on 5R, Xcfe124, -159 and -277 on 6R, Xcfe010, -143 and -228 on 7R. With the exception of Xcfe159 and Xcfe224, all the Xcfe loci mapped were found in orthologous positions considering multiple evolutionary translocations in the rye genome relative to those of common wheat. The consensus map was constructed using mapping data from the four bi-parental populations. It contains a total of 123 microsatellites, 12 SNPs, 118 RFLPs and 2 isozyme loci.